2003
DOI: 10.1021/jp034911h
|View full text |Cite
|
Sign up to set email alerts
|

Spray-Ion Layer Gas Reaction (ILGAR)a Novel Low-Cost Process for the Deposition of Chalcopyrite Layers up to the Micrometer Range for Photovoltaic Applications

Abstract: A novel variant of the ion layer gas reaction (ILGAR) process is described. Up to now, only layers with a maximum thickness of about 100 nm could be deposited by ILGAR in a reasonable time. Replacing of dipping by spraying on a warm substrate accelerated the application of the precursor solution (e.g., metal chloride in water) by a factor of at least 100. For multinary products, all precursors are applied either simultaneously as a mixed solution or sequentially. In intervals, the spraying is stopped and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…This shows that the thickness of the TiO 2 film on stainless steel was only influenced by the spraying time, and not so much by the concentration of the TiO 2 precursor and heating temperature. This is in accordance with the findings of Fischer et al [8] where they reported that a reasonable time of deposition by ILGAR is needed in order to obtain layers with a maximum thickness of about 100 nm.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This shows that the thickness of the TiO 2 film on stainless steel was only influenced by the spraying time, and not so much by the concentration of the TiO 2 precursor and heating temperature. This is in accordance with the findings of Fischer et al [8] where they reported that a reasonable time of deposition by ILGAR is needed in order to obtain layers with a maximum thickness of about 100 nm.…”
Section: Resultssupporting
confidence: 93%
“…When the spraying duration was shortened to 6 min, some parts of the stainless steel were uncoated by the TiO2 (Figure 3a). This is most probably caused by insufficient spraying time for the layer to form [8]. The thickness measurement also supports this hypothesis.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Numerous research papers reporting synthesis of CuS in thin films [8][9][10][11][12][13][14][15][16][17][18], nanoparticles [19][20][21][22][23][24][25][26][27][28][29][30], micro-meter size morphologies [31,32], etc. forms have been reported.…”
Section: Introductionmentioning
confidence: 99%